Reactions of bone, liver and kidney tissues to orthopaedic implants with silver nanoparticle doped hydroxyapatite coatings: microscopic examination in a rabbit model (Journal of Medical Science, 2018)
Background: Periprosthetic joint infections are severe complications of arthroplasty, difficult to manage due to biofilm formation on the components. Recently, the use of silver nanoparticles (SNs) has emerged as a method of preventing biofilm formation on orthopaedic implants, however little is known about the systematic toxicity of SNs. Aim: This study used a rabbit model to examine the tissue response of bone, liver and kidney to prototype components with SN doped hydroxyapatite (HA) coatings. Materials and methods: Twelve prototype implants (six with HA, six with SN doped HA coatings) were implanted into the femora of twelve New Zealand Rabbits. After 6 weeks, the animals were euthanised, their femora and samples of livers and kidneys harvested to prepare microscopic slides. The slides were examined for the presence inflammatory or toxic reactions to SNs, implants were examined using scanning electron microscopy (SEM) to determine structural changes related to implantation and verify retention of SNs in vivo. Results: SEM demonstrated that SNs formed submicron conglomerates, which were retained after 6 weeks in vivo and did not interfere with osseointegration. Histologic studies of bone fragments demonstrated no signs of acute toxicity and inflammation. No inflammatory reaction was observed in kidneys, although in some samples signs of acute renal failure related to euthanasia were found. No severe toxic reaction was found in liver samples, however fatty degeneration of liver was found in some animals. Conclusions: This study documented good osteointegration of implants with SN doped HA coatings with low systematic toxicity of SNs.